Ентеротоксогени соеви на стафилококи во млечната индустрија во Р.С. Македонија - Раткова Мановска, Марија (Факултет за ветеринарна медицина, УКИМ, Скопје, 2021)
Staphylococci are ubiquitous microorganisms and can be present on various surfaces in the environment and animals, food production equipment, food as well as humans. One of the most important representatives of the genus is Staphylococcus aureus, a significant pathogen for animals and humans, primarily due to the virulent properties it may possess as a result of a combination of genes that produce toxins, invasive components and antibiotic resistance. The ability of the strains of S. aureus to produce one or more staphylococcal enterotoxins (SEs) is associated with the occurrence of staphylococcal food poisoning, which occurs when ingesting the food it contains. The occurrence of S. aureus food intoxications is usually listed as the third or fourth most common foodborne illness in many countries (after poisonings caused by Salmonella spp., Campylobacter spp., Clostridium perfringens, and sometimes E. coli O157). For the purposes of this research, a total of 1662 samples were analyzed, including 333 samples of milk, 1160 samples of dairy products and 169 samples of swabs in a period of 5 years (2016-2020). The strains were detected and confirmed according to ISO 6888-1 "Horizontal method for enumeration of coagulase positive staphylococci". Phenotypic identification of the strains was determined using GP cards of the Vitek 2 automated identification system (Biomerieux, France). The mini VIDAS SET2 test kit, which works as an enzyme-linked fluorescence test (ELFA), was used for phenotypical detection of the ability of strains to produce enterotoxins. Antimicrobial resistance of the strains was also phenotypically determined with Vitek 2, AST P-580 card. Molecular analyzes of the isolates included: identification of the 23s gene of S. aureus, nuc gene, detection of 11 genes for the production of enterotoxins (sea, seb , sec, sed, see, seg, seh, sei, ser, sej and sep), 5 genes for biofilm production (icaA, icaB, icaC, icaD and bap) and the mecA gene carrying methicillin resistance. We determined presence of 215 (12.9%) strains of staphylococci in total, with a prevalence of coagulase positive 9.6% and coagulase negative staphylococci 3.4%. According to the enumeration, 4.8% of the raw milk samples and 0.7% of the dairy products were unsatisfactory according to the relevant legislation. The most common isolate was S. aureus with 73.2% in milk isolates and 68.4% in dairy isolates, while the most common in swabs was S. epidermidis 37.5%. Using the PCR method, S. aureus was detected in a larger number of isolates compared to the phenotypic method. S. aureus strains possessed the nuc gene in 98.9% / 97.9% / 66.7% of milk / dairy products / swab isolates, respectively. With the phenotypic method for detecting of SEs production, mini VIDAS SET2, 41 isolates (33.3%) from milk isolates, 29 (38.2%) from dairy products and 2 (12.5%) from swabs gave a positive reaction. By PCR, genes for the production of SEs were detected in 85 (69.1%) strains in milk, 38 (50%) in dairy products and 5 (31.6%) in swabs. A total of 18 enterotoxogenic isolates from all samples were not S. aureus. The molecular method identified 10 of the 11 genes examined, the most common being seg and sei, no isolates with the see gene were detected, and there were isolates carrying from 1 to 5 genes. Genes for biofilm production were detected in 58.5% of milk isolates, 67.1% of dairy isolates and 56.3% of swab isolates. Phenotypically, the highest resistance of milk and dairy strains was detected against the aminoglycoside group of antibiotics, then to β-lactams, while in swab isolates it was the other way around. A total of 15 strains phenotypically showed methicillin resistance, of which 6 were non-S. aureus staphylococci. The methicillin mecA resistance gene was identified in 9 isolates, 4 of which were not S. aureus. These results indicate the presence of enterotoxogenic strains of different types of staphylococci in the tested samples, which imposes the need to take appropriate prevention, such as proper sanitation and hygienic practice, use of safe raw materials, proper habits when handling finished products and the need for further monitoring of the condition with SEs in order to have safe food and prevention of intoxication.
Докторска дисертација одбранета во 2021 година на Факултетот за ветеринарна медицина во Скопје, под менторство на проф. д–р Павле Секуловски.
Keywords: milk, dairy products, staphylococci, S. aureus, enterotoxins, PCR, biofilm genes, methicillin-resistance